Ergonomic Evaluation on Chicken Feeder Tool at Egg-Laying Chicken Farm SME - Nilda Tri Putri; Elita Amrina; Dicky Fatrias; Insannul Kamil; Nabila Humaida (Jurnal Optimasi Sistem Industri, 2021)
This research aims to evaluate the egg-laying chicken feeder that was designed at egg-laying chicken farm small and medium enterprise (SME). The main reason of this tool design was due to the worker’s complain of feeling pain during the feeding process. Evaluation was performed based on Nordic Body Map questionnaire result, physiological workload, and NIOSH lifting equation calculation. The observed work ranged from the feed filling in the basket until all feeds were distributed. The results showed that the %CVL was in the range of 18%-30% and the energy consumption of workers was in the range of 1.24-3.00 Kcal/minute. Thus, physiologically, the work activities carried out by the feed workers were categorized as very light workload. Meanwhile, evaluation using Lifting Index (LI) methods in the process of feeding showed the LI value ranged from 0.9-1, therefore this activity is safe to perform manually. Based on the prototype evaluation on the feeding aid, the process of feeding activities was more effective 1.5 times faster than the old tools. In addition, with the use of this new tool, the feeding process was easier to adjust the dose each time.